Rectal spacer use and overall long-term healthcare costs: payer perspective - Yu, James B.; Sato, Ryoko; Folkert, Michael R.; Bhattacharyya, Samir; Ezekekwu, Emmanuel; Hamstra, Daniel A. (Frontiers in Oncology, 2025)
IntroductionRectal spacers (RS), when used in prostate cancer (PCa) patients treated with radiotherapy (RT), reduce radiation dose to the rectum. While RS incur additional upfront cost, they may result in long-term cost-savings by reducing toxicity-related adverse events and associated medical costs. This study examined long-term pattern of insurer-paid healthcare costs among patients with and without polyethylene glycol hydrogel RS use.MethodsMen with PCa who received RT during 2015–2020 were identified from Medicare 5% and Merative™ MarketScan Commercial data. Multivariable generalized linear models assessed the association between RS utilization and total costs from 1-year prior to RT to 4- years after RT, controlling for age, comorbidity, RT modality, secondary cancer, baseline dysfunction, data source, year of RT, and state. Analyses were stratified by payer type (Medicare, commercial) and cost type (overall, those for specific conditions).ResultsThe analysis included 5,829 individuals, 270 (4.6%) of whom received RS. After controlling for covariates, costs 1-year pre-RT were significantly higher for RS patients by +$1,811 ($17,378 vs. $15,567, p=0.023), as were costs for RT (including RS) at the time of treatment by +$3,949 ($31,712 vs. $27,763, p<0.001). However, total insurer paid costs over the following 4 years post-RT were significantly lower for RS patients by $8,095 ($52,345 vs. $60,440, p=0.011). Similar patterns were observed when examining costs related to bowel, sexual, or urinary dysfunction separately.ConclusionsPatients with RS use undergoing PCa RT had significantly lower long-term overall healthcare costs despite incurring higher initial costs prior to and during RT, suggesting that upfront investment in RS may be offset by long-term savings for insurers.